Characterization of a novel alkaline β-agarase and its hydrolysates of agar. (15th October 2019) - Chen, Xinglin; Lin, Hetong; Jin, Min; Zeng, Runying; Lin, Mengshi
Highlights: A novel gene aga3027 from Flammeovirga sp. OC4 was screened and expressed in E. coli. Recombinant Aga3027 belongs to the glycoside hydrolase (GH) 16 subfamily of agarase. Recombinant Aga3027 manifested the maximum activity of agarase at 40 °C and pH 9.0. Recombinant Aga3027 showed thermostability (30–40 °C) and pH-stability (pH 6.0–9.0). Neoagarotetraose and neoagarohexaose from agar by recombinant Aga3027 were identified. Abstract: A novel gene aga3027 from the genome of Flammeovirga sp. OC4, isolated from the deep sea, was screened and expressed in Escherichia coli BL21. This gene encoded the genetic information of a potential agarase that consists of 851 amino acids and belongs to 16 β -agarase family of glycoside hydrolase. Purified recombinant Aga3027 demonstrated the maximum activity of agarase at 40 °C and pH 9.0, displaying excellent thermostability and pH-stability. The agarase retained more than 80% of its maximum activity after incubation at 30–40 °C for 48 h, or after incubation at pH 6.0–9.0 for 60 min, which indicated that this agarase was suitable for industrial applications. Silica gel chromatography was used to purify the hydrolysates of agar treated by agarase from the recombinant Aga3027. The hydrolysates were identified as neoagarotetraose and neoagarohexaose by thin layer chromatography and further confirmed by ion chromatography.